The rise of the Phoenix or an Achilles heel? : Breaking New Ground's impact on urban sustainability and integration - Smith, Tarryn Nicole Kennedy (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Geography and Environmental Studies)--University of Stellenbosch, 2010.